Diameter Effect on the Wall Temperature Behaviors During Supercritical Water Heat Transfer Deterioration in Circular Tubes and Annular Channels - Cheng, Hui; Yanlin, Aaron Bai; Wang, Jun; Zhao, Jiyun (Frontiers in Energy Research, 2019)
Diameter effect on heat transfer deterioration (HTD) was numerically studied for supercritical water flowing upward in circular tubes and annular channels at high heat flux and low mass flux based on validated turbulence model. When the same boundary conditions were applied, i.e. heat flux, mass flux, and inlet temperature, it was found that in circular tubes the first wall temperature peak moves upstream and the magnitude of the peak increases first and then decreases with the increase of tube diameter, the second peak moves downstream with the increase of tube diameter. Whereas in annular channels with a fixed inner diameter, HTD is suppressed when the outer diameter is small and HTD occurs gradually with the increase of outer diameter. These phenomena are consistent with previous experimental results. The mechanism was analyzed based on fully developed turbulent velocity profile at the inlet of the heated sections. Increasing inner diameter for circular tubes or outer diameter for annular channels will result in the decrease of maximum velocity and velocity gradient in the near wall region, which makes velocity profile in this region much easier to be flattened by the buoyancy. Then an M-shaped velocity profile is formed, which will significantly decrease the Reynolds shear stress and turbulent kinetic energy and hence impair the heat transfer and cause HTD. For the same flow conditions, HTD is much easier to occur in circular tubes than in annular channels with the same hydraulic diameters.